Kreativitas dan Ketahanan Emosional pada Siswa dengan Ekskul Membatik - Evi Afifah Hurriyati; Ratri Dyah Mawarni (Humaniora, 2013)
Batik is not only an element of culture and art, but it has creativity. Batik also has the message how to manage our emotions, because in making batik takes perseverance, optimism, cognitive function as well as patience. The aim of this research was to examine the relationship between creativity and emotional resiliency in students grade 4-6 elementary school. Subjects were students of MI Giriloyo 2 Yogyakarta grade 4 to grade 6, which amounted to 62 students. Data retrieval is done by spreading the figural creativity tests to measure creativity variables and emotional resilience questionnaire to measure the variables of emotional resilience. Subjects showed a fairly good creativity with emotional resilience pretty good anyway. Bivariate product moment correlation with SPSS 19.0 for windows between creativity with emotional resilience correlation values obtained at 0.184 and p = 0.153. Research shows that the zero hypothesis (H0) which states "There is no significant relationship between creativity and emotional resiliency in students MI Giriloyo 2 Yogyakarta" accepted while the alternative hypothesis (Ha) which states "There is a significant relationship between creativity and emotional resilience MI students Giriloyo 2 Yogyakarta” had rejected. Thus, the results showed no relationship between creativity and resilience significant emotions in students with extracurricular student-MI batik Giriloyo 2 Yogyakarta with a very low correlation coefficient. Other variables were not examined by the authors, such as internal and external factors correlated with the subjects supposedly more emotional resilience.